Christine Cristina - Sandrelli, Amanda; Boni, Alessio 1966-; Haber, Alessandro 1947- (CG Home Video S.R.L., 2010)
Explores the life of Christine de Pisan, the Venetian-born poet of the 15th century, who spent most of her life at the court of Charles V in Paris